Pengembangan Strategi Bisnis Menggunakan Analisis SWOT pada CV DejeeFish Sukabumi - Muhamad Hasan Taufik; Vira Agustin Pratiwi; Novita Fauzi; Fikri Bambang Somantri (Journal of Management and Social Sciences, 2024)
The SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis is widely known and commonly applied in business strategy. CV Dejeefish was chosen for this SWOT analysis to help develop the company’s business strategy. The objective of this study is to identify the impact of SWOT analysis on business development and to uncover weaknesses, obstacles, and areas for improvement that could enhance the company’s efficiency, quality, and sustainability. The findings indicate that CV Dejeefish is in a relatively strong position, with more strengths than weaknesses and threats. However, CV Dejeefish still needs to implement a combination of SWOT-based business strategies and a SWOT Matrix. Firstly, in the SO (Strengths-Opportunities) strategy, the company can leverage high-quality broodstock from BBAT to expand its market, adopt the latest technology in aquaculture, and develop value-added products. Secondly, in the WO (Weaknesses-Opportunities) strategy, expanding the use of aquaculture technology and improving responsiveness to climate change and market conditions is strongly recommended. For the ST (Strengths-Threats) strategy, a focus on strict quality control, risk mitigation, and maintaining adequate capital reserves is necessary to address potential threats. Lastly, the WT (Weaknesses-Threats) strategy should involve implementing effective monitoring systems, building strong relationships with stakeholders, and conducting regular evaluations.